VD_FINDINFO Pron / 2013 / 56 vom 4. März 2013 - VD Tribunal cantonal (2013)
TRANSACTION JUDICIAIRE, PROTECTION DE L'UNION CONJUGALE, FRAIS JUDICIAIRES | 105 al. 1 CPC (CH), 241 al. 2 CPC (CH), 65 al. 2 TFJC (2010), 67 al. 2 TFJC (2010)